FEASIBILITY ANALYSIS OF USING BIOGAS RECOVERY FROM PALM OIL MILL EFFLUENT - dkk, Subiyanto (BPPT)
The increasing of crude palm oil (CPO) production in Indonesia is followed by the increasing of palm oil mill effluent. Unfortunately, the open system effluent treatment carried out by most of the palm oil mills potentially generates methane gas emission and increases greenhouse gas concentration in the atmosphere. This study proposes of using methane gas recovery for alternatively flaring and generating electricity, and analyze it in the framework of Clean Development Mechanism. Samples of effluent were taken from the three size of palm oil mills (60, 40, and 30 tonnes per hour of empty fresh bunch) in north Sumatra. The results indicate that capturing methane gasfrom the palm oil mill effluent and using the biogas for generating electricity mainly and flaring the rest will reduce carbon emissions as well as generate the additional income for the palm oil mill business.keywords : POME, methane, carbon emission, generating electricity, feasibility analysis of business